Legal and Ethics in Business : Navigating Key Principles and Compliance for Modern Enterprises. - Online Courses, Virversity. (Virversity Online Courses: Legal and Ethics Series, 2025)
This book provides a comprehensive exploration of legal and ethical principles essential for modern business operations. It covers foundational topics such as contract law, business structures, employment law, intellectual property, consumer protection, and regulatory compliance. The book emphasizes the importance of ethical decision-making and risk management in maintaining corporate integrity. Designed for business professionals and students, it aims to equip readers with practical knowledge to navigate complex legal environments, resolve disputes, and ensure compliance with laws governing enterprises. The course also includes insights into international business law, environmental compliance, and effective dispute resolution strategies, offering an invaluable resource for those seeking to excel in business law and ethics.